Species-Specific Colocalization of Middle East Respiratory Syndrome Coronavirus Attachment and Entry Receptors - Widagdo, W; Okba, Nisreen M A; Li, Wentao; de Jong, Alwin; de Swart, Rik L; Begeman, Lineke; van den Brand, Judith M A; Bosch, Berend-Jan; Haagmans, Bart L (Journal of virology, 2019)
Middle East respiratory syndrome coronavirus (MERS-CoV) uses the S1 domain of its spike protein to bind to dipeptidyl peptidase 4 (DPP4), its functional receptor, and its S1 domain to bind to sialic acids. The tissue localization of DPP4 in humans, bats, camelids, pigs, and rabbits generally correlates with MERS-CoV tropism, highlighting the role of DPP4 in virus pathogenesis and transmission. However, MERS-CoV S1 does not indiscriminately bind to all α2,3-sialic acids, and the species-specific binding and tissue distribution of these sialic acids in different MERS-CoV-susceptible species have not been investigated. We established a novel method to detect these sialic acids on tissue sections of various organs of different susceptible species by using nanoparticles displaying multivalent MERS-CoV S1 We found that the nanoparticles specifically bound to the nasal epithelial cells of dromedary camels, type II pneumocytes in human lungs, and the intestinal epithelial cells of common pipistrelle bats. Desialylation by neuraminidase abolished nanoparticle binding and significantly reduced MERS-CoV infection in primary susceptible cells. In contrast, S1 nanoparticles did not bind to the intestinal epithelium of serotine bats and frugivorous bat species, nor did they bind to the nasal epithelium of pigs and rabbits. Both pigs and rabbits have been shown to shed less infectious virus than dromedary camels and do not transmit the virus via either contact or airborne routes. Our results depict species-specific colocalization of MERS-CoV entry and attachment receptors, which may be relevant in the transmission and pathogenesis of MERS-CoV. MERS-CoV uses the S1 domain of its spike protein to attach to its host receptor, dipeptidyl peptidase 4 (DPP4). The tissue localization of DPP4 has been mapped in different susceptible species. On the other hand, the S1 domain, the N-terminal domain of this spike protein, preferentially binds to several glycotopes of α2,3-sialic acids, the attachment factor of MERS-CoV. Here we show, using a novel method, that the S1 domain specifically binds to the nasal epithelium of dromedary camels, alveolar epithelium of humans, and intestinal epithelium of common pipistrelle bats. In contrast, it does not bind to the nasal epithelium of pigs or rabbits, nor does it bind to the intestinal epithelium of serotine bats and frugivorous bat species. This finding supports the importance of the S1 domain in MERS-CoV infection and tropism, suggests its role in transmission, and highlights its potential use as a component of novel vaccine candidates.